Novel real-time remote audio-visual aided technique for doffing of personal protective equipment and assessment of satisfaction level among front-line health care workers amid COVID-19 pandemic - Kaur, Sukhpal; Kaur, Damanpreet; Singh, Ajay; Lazar, Michelle Shirin; Saini, Sushma; Dhandapani, Manju; Soni, Shiv Lal; Naik, Naveen B.; Ganesh, Venkata; Das, Karobi; Puri, Goverdhan Dutt (International Journal Of Community Medicine And Public Health, 2021)
Background: Appropriate and cautious doffing is vital to prevent self-contamination and infection from the highly contagious SARS-CoV-2 virus. In current study satisfaction levels of front-line health care workers regarding doffing assisted by a novel real-time remote audio-visual aided approach was assessed. Methods: A questionnaire-based survey was carried out among 158 health care workers. The questionnaire was developed and validated to assess the participants’ satisfaction level regarding the instructions being given remotely for doffing through the real-time remote audio-visual aided technique pertaining to the various facilities available for doffing, remote communication for doffing steps, audio-visual technical issues, rectification of the breach in safety and the level of anxiety. Results: The survey received a 79% response rate. 74.6% of the respondents were highly satisfied. 61.9% agreed on the adequacy of doffing space, 70.9% strongly agreed/agreed regarding the availability of adequate equipment, 78.5% strongly agreed/agreed with the instructions. The overall median (IQR) satisfaction score was 9 (8-10). Conclusions: Real-time remote audio-visual aided doffing approach is a simple, technology-aided strategy that is shown to enhance the satisfaction and motivation of the health care workers. This can potentially help in reducing the number of personnel required in directly monitoring doffing leading to freeing up more people to work with the patients while reducing unnecessary exposure. This translates to effective utilisation of resources. The high satisfaction associated with the use of this system boosts the feasibility of its implementation in every tertiary care setup.